Quasi-Static Crushing Behavior of Nomex Honeycomb Filled Thin-Walled Aluminum Tubes - Çakıroğlu, Cem; Güden, Mustafa (Izmir Institute of Technology, 2008)
The experimental and numerical studies presented in this thesis were focused on the experimental and numerical quasi-static crushing behavior of Nomexl1 honeycomb filled thin-walled aluminum tubes. Nomexl1 honeycombs having different cell sizes (3.2, 4.8 and 6.4 mm) and the same density (48 kg/m3) were used to fill thin walled aluminum tube, 25 mm in diameter and 0.29 mm in thickness. Compression tests were conducted at quasi-static the strain rates of 1.64 10-2, 6.56 10-3 and 3.28 10-3 s-1. The results showed that the honeycomb cell size had a strong effect on the crushing behavior. Decreasing cell size increased crushing loads and the specific absorbed energy values of empty tubes. The highest strengthening effect of filling was found in 3.2 mm cell size honeycomb filled tubes. Although no effects of 4.8 and 6.4 mm cellsize honeycomb filling on the deformation mode of tube was observed (mixed), 3.2 mm cell size honeycomb filling changed the deformation mode to mixed/concertina. The numerical model of empty tube, 6.4 mm cell size honeycomb and 6.4 mm cell size honeycomb filled tube were performed using LS-DYNATM and ANSYSTM finite element analysis programs. To acquire maximum computational efficiency, a mesh optimization was done. The effect of the honeycomb cell wall thickness was also investigated numerically and shown to have a strong effect on the crushing behavior of honeycomb. The experimental and numerical studies conducted showed that 3.2 mm cell size Nomex® honeycomb might become an alternative to aluminum foam filler in thin walled tubes as long as the tube crushing load was comparable with honeycomb crushing load.
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2008
Includes bibliographical references (leaves: 78-81)
Text in English; Abstract: Turkish and English
xiv, 96 leaves
Keywords: TA492. C13 2008; Tubes; Aluminum tubes; Honeycomb structures